Image georectification and feature tracking toolbox: ImGRAFT - Messerli, A.; Grinsted, A. (Geoscientific instrumentation, methods and data systems, 2015)
The use of time-lapse camera systems is becoming an increasingly popular method for data acquisition. The camera setup is often cost-effective and simple, allowing for a large amount of data to be accumulated over a variety of environments for relatively minimal effort. The acquired data can, with the correct post-processing, result in a wide range of useful quantitative and qualitative information in remote and dangerous areas. The post-processing requires a significant amount of steps to transform images into meaningful data for quantitative analysis, such as velocity fields. To the best of our knowledge at present a complete, openly available package that encompasses georeferencing, georectification and feature tracking of terrestrial, oblique images is still absent. This study presents a complete, yet adaptable, open-source package developed in MATLAB, that addresses and combines each of these post-processing steps into one complete suite in the form of an "Image GeoRectification and Feature Tracking" (ImGRAFT: http://imgraft.glaciology.net) toolbox. The toolbox can also independently produce other useful outputs, such as viewsheds, georectified and orthorectified images. ImGRAFT is primarily focused on terrestrial oblique images, for which there are currently limited post-processing options available. In this study, we illustrate ImGRAFT for glaciological applications on a small outlet glacier Engabreen, Norway.